Expanding Germany's relations with India: Triangular cooperation as the next step in the strategic partnership - Christian Wagner; Jana Lemke; Tobias Scholz (Stiftung Wissenschaft und Politik (SWP), 2022)
India is a central partner for German and European foreign policy in the Indo-Pacific. The German Federal Government's autumn 2020 guidelines and the November 2021 coalition agreement both emphasise the importance of expanding relations with India. To advance the common cause of a multilateral and rules-based order in the Indo-Pacific, both sides should - in addition to deepening their bilateral relations - extend their cooperation to third countries. Such triangular cooperation could herald a new phase of the Indo-German strategic partnership.
Keywords: 320